KEMAMPUAN MENYIMAK WACANA DESKRIPSI SISWA KELAS V SD ALKHAIRAAT I PALU - Mardiah Mardiah (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
The purpose of this study is (1) To describe the ability of Grade V students of SD Alkhairaat I Palu in listening to description discourse. (2) To describe the factors that become obstacles and solutions in the implementation of listening to the discourse description of the fifth grade students of SD Alkhairaat I Palu. The author chose the title of this research because listening learning is a very important skill to improve students' reasoning power in all fields of study, especially in the area of ​​Indonesian Language studies. This study uses a descriptive method with data collection techniques of observation, interviews, recorders, questionnaires and evaluations, the final results of the researchers showed that the average value of 82 students obtained grade V SD Alkhairaat I Palu in listening to the discourse description including the category category of grades is quite good